Clinical Decision Making when Addressing Upper Limb Post-Stroke Sensory Impairments. (June 2013) - Doyle, Susan; Bennett, Sally; Gustafsson, Louise
Introduction: This study explored factors influencing occupational therapists' clinical decision making when choosing to assess upper limb post-stroke sensory impairments (ULPSSI) and selecting interventions. Method: A survey of 187 American occupational therapists working with stroke survivors. Findings: Respondents most commonly assessed ULPSSI to determine the impact on occupational performance and guide interventions, and most commonly did not undertake assessment if clients either reported no impairments or were unable to participate in testing. Being unaware of interventions, believing motor interventions addressed ULPSSI and lack of time most commonly led to the decision not to use interventions for ULPSSI. Clients' cognitive status, severity of ULPSSI and time since stroke influenced therapists when choosing between compensatory or remedial approaches. Prior experience, effects seen when trialling interventions and consulting other therapists most commonly influenced specific intervention choice. Conclusion: Deciding to assess ULPSSI was influenced by theoretical knowledge and domain-specific clinical knowledge while decisions about interventions were largely influenced by the therapists' domain-specific clinical knowledge, clinical experience and by specific contextual factors such as time available for therapy. Respondents used both automatic and reflective or deliberate decision-making processes. Education on evidence-based interventions and strategies for decision making in areas of clinical uncertainty is warranted.